Ombo apyka. conception and Birth among Mbyá guaraní - Enriz, Noelia (2010)
This paper examines the practices related to pregnancy, birth, naming, and circulation of children in order to approach to their socially constructed place among the Argentine’s Mbyá Guaraní. I begin by arguing that the religious values are central to their production as people. Then I examine some non-ordinary and disruptive situations, such as the conception and birth of twins, to show how a Mbyá person settles down in the group. Finally, I consider the exceptions to the traditional ways for they show that in the Mbyá worldview, new mechanisms of inclusion of children have been generated.